Efficient starch recovery from cassava bagasse: role of cellulase and pectinase - Anh, Pham Tuan; Ngan, Pham Kim; Anh, To Kim (Vietnam Journal of Science and Technology, 2019)
In this paper, the bagasses were treated with single pectinase (Pectinex Ultra SP-L, Novozymes) and cellulase (NS22192, Novozymes) or their mixture at various enzyme ratio. The response surface methodology was used to fit the experimental data and investigate the enzyme ratio influence on the starch recovery yield. The highest starch yield was achieved in the treatment of bagasse with 15 CMCU and 9PGU per gram of dry bagasse at 450C and pH 5 for 4 hours at the solid loading 5%, attained 86.55% of the residue starch.